(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify: .Self-composition of the kindergarten students1 2.Recognizing the differences in self-authoring according to the study ROWS(first, second, third, fourth). To Achieve The Objectives Of The Current Research, The Researcher Chose The Research Community From The Students Of The Kindergarten Department _ College Of Basic Education / Al-Mustansiriya University. The Subjective,Whose Number Of Paragraphs Amounted To (48) Items, And After Extracting The Psychometric Characteristics Of Validity And Reliability Using Statistical Methods (Arithmetic Mean, And Standard Deviation, And T-test For One Sample, And T-test For Two Independent Samples, And Pearson Correlation Coefficient, And Cronbach’s Alpha Coefficient, And One-Way Alanalysis Of Variance, And Scheffe Equation For Dimensional Comparisons) , The Final Formula For The Two Scales Was Produced And Applied To The Basic Sample. After processing The Data Statistically, The Researcher Reached The Following: Kindergarten students have good self-writing. .1 2.Female students of the first stage have more self-composition than others in the other stages. Based on the findings, the researcher made some recommendations and suggestions related to the research variable.